Eradication of Biofilms on Catheters: Potentials of Tamarix ericoides Rottl. Bark Coating in Preventing Catheter-Associated Urinary Tract Infections (CAUTIs) - Mohammed H. Karrar Alsharif; Muhammad Musthafa Poyil; Salman Bin Dayel; Mohammed Saad Alqahtani; Ahmed Abdullah Albadrani; Zainab Mohammed M. Omar; Abdullah MR. Arafah; Tarig Gasim Mohamed Alarabi; Reda M. Fayyad; Abd El-Lateef Saeed Abd El-Lateef (Life)
Catheter-associated urinary tract infections (CAUTIs) cause serious complications among hospitalized patients due to biofilm-forming microorganisms which make treatment ineffective by forming antibiotic-resistant strains. As most CAUTI-causing bacterial pathogens have already developed multidrug resistance, there is an urgent need for alternative antibacterial agents to prevent biofilms on catheter surfaces. As a trial to find out such a potential agent of natural origin, the bark of Tamarix ericoides Rottl., a little-known plant from the Tamaricaceae family, was examined for its antibacterial and antibiofilm activities against one of the major, virulent, CAUTI-causing bacterial pathogens: Enterococcus faecalis. The methanolic T. ericoides bark extract was analyzed for its antibacterial activity using the well diffusion method and microdilution method. Killing kinetics were calculated using time–kill assay, and the ability of biofilm formation and its eradication upon treatment with the T. ericoides bark extract was studied by crystal violet assay. GC-MS analysis was performed to understand the phytochemical presence in the extract. A in vitro bladder model study was performed using extract-coated catheters against E. faecalis, and the effect was visualized using CLSM. The changes in the cell morphology of the bacterium after treatment with the T. ericoides bark extract were observed using SEM. The biocompatibility of the extract towards L929 cells was studied by MTT assay. The anti-E. faecalis activity of the extract-coated catheter tube was quantified by viable cell count method, which exposed 20% of growth after five days of contact with E. faecalis. The anti-adhesive property of the T. ericoides bark extract was studied using CLSM. The extract showed potential antibacterial activity, and the lowest inhibitory concentration needed to inhibit the growth of E. faecalis was found to be 2 mg/mL. The GC-MS analysis of the methanolic fractions of the T. ericoides bark extract revealed the presence of major phytochemicals, such as diethyl phthalate, pentadecanoic acid, methyl 6,11-octadecadienoate, cyclopropaneoctanoic acid, 2-[(2-pentylcyclopropyl) methyl]-, methyl ester, erythro-7,8-bromochlorodisparlure, etc., that could be responsible for the antibacterial activity against E. faecalis. The killing kinetics of the extract against E. faecalis was calculated and the extract showed promising antibiofilm activity on polystyrene surfaces. The T. ericoides bark extract effectively reduced the E. faecalis mature biofilms by 75%, 82%, and 83% after treatment with 1X MIC (2 mg/mL), 2X MIC (4 mg/mL), and 3X MIC (6 mg/mL) concentrations, respectively, which was further confirmed by SEM analysis. The anti-adhesive property of the T. ericoides bark extract studied using CLSM revealed a reduction in the biofilm thickness, and the FDA and PI combination revealed the death of 80% of the cells on the extract-coated catheter tube. In addition, SEM analysis showed extensive damage to the E. faecalis cells after the T. ericoides bark extract treatment, and it was not cytotoxic. Hence, after further studies, T. ericoides bark extract with potential antibacterial, antibiofilm, and anti-adhesive activities can be developed as an alternative agent for treating CAUTIs.